Contributions of Botanists of Natural History Museum (Tribhuvan University) to Research and Education in Nepal - Dangol, Dharma Raj (Journal of Natural History Museum, 2018)
This paper deals with the contribution of botanists of Natural History Museum,Tribhuvan University, Nepal in the field of plant research and education. Of the 14 listed, only two botanists are continuing their service in the museum. Their research works mainly focused on collection and exploration of flora, supervision of dissertation including publication of 171 articles in different journals of national and international repute. Apart from this, their contributions in education/training by organizing seminars/trainings/workshops are highly significant.J. Nat. Hist. Mus. Vol. 29, 2015, Page: 122-147